Radiographic views of digestive tracts of rainbow trout (Oncorhynchus mykiss) and mirror carp (Cyprinus carpio - Çalta, Metin (My University, 2016)
In this study, radiographic views of digestive tracts of rainbow trout [Oncorhynchus mykiss (Walbaum, 1792)] and mirror carp (Cyprinus carpio Linnaeus, 1758) were investigated. For this purpose, barium sulphate suspension was used as contrast agent. This agent was given into fish digestive tracts from the anus using a syringe. Then X-ray radiographs of fishes were taken. It was found that there were quite big differences between rainbow trout and mirror carp in term of structure of digestive tract. In comparison, digestive tract of rainbow trout is shorter because of possessing short intestine, anatomic stomach and pyloric caeca are present. However, digestive tract of mirror carp is very longer because of possessing long intestine and anatomic stomach is absent.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Oncorhynchus mykiss; Cyprinus carpio; Digestive Tract; Rainbow trout; Mirror carp; Digestive tract